Phylogeography and demographic history of the neotropical otter (Lontra longicaudis) - Trinca, Cristine Silveira; Thoisy, Benoît de; Weber Rosas, Fernando Cesar; Waldemarin, Helen Francine; Koepfli, Klaus Peter; Vianna, Juliana A.; Eizirik, Eduardo (Journal of Heredity, 2012)
The Neotropical otter (Lontra longicaudis) is a medium-sized semiaquatic carnivore with a broad distribution in the Neotropical region. Despite being apparently common in many areas, it is one of the least known otters, and genetic studies on this species are scarce. Here, we have investigated its genetic diversity, population structure, and demographic history across a large portion of its geographic range by analyzing 1471 base pairs (bp) of mitochondrial DNA from 52 individuals. Our results indicate that L. longicaudis presents high levels of genetic diversity and a consistent phylogeographic pattern, suggesting the existence of at least 4 distinct evolutionary lineages in South America. The observed phylogeographic partitions are partially congruent with the subspecies classification previously proposed for this species. Coalescence-based analyses indicate that Neotropical otter mitochondrial DNA lineages have shared a rather recent common ancestor, approximately 0.5 Ma, and have subsequently diversified into the observed phylogroups. A consistent scenario of recent population expansion was identified in Eastern South America based on several complementary analyses of historical demography. The results obtained here provide novel insights on the evolutionary history of this largely unknown Neotropical mustelid and should be useful to design conservation and management policies on behalf of this species and its habitats. © The American Genetic Association. 2012. All rights reserved.
Keywords: Dna, Mitochondrial; Base Pairing; Carnivora; Genetic Variability; Lontra Longicaudis; Neotropics; Nonhuman; Nucleotide Sequence; Phylogeography; Population Structure; Priority Journal; Sequence Analysis; Animal; Dna, Mitochondrial; Evolution, Molecular; Genetic Variation; Otters; Phylogeography; Species Specificity; Lontra Longicaudis; Lutrinae; Mustelidae